Evaluation of Wastewater and Hazardous Waste Management Planning in Hospital X, Jakarta - Andina Ilma Darmawan; Mega Mutiara Sari; I Wayan Koko Suryawan (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2022)
Environmental permits from hospital activities must meet good solid and liquid waste management. Hospital waste management is closely related to patients' infectious status, so it is dangerous and toxic. One that can be used as a reference is a study of the construction of Hospital X in the Cengkareng area, West Jakarta. The purpose of this study was to evaluate waste management for environmental permits from the activities of Hospital X. This study was conducted using field observation techniques. Wastewater that is treated from an activity produced in health care facilities consists of domestic wastewater, clinical wastewater, laboratory wastewater, etc. The WWTP planning design that several health care facilities have widely used has an aerobic biofilter system that requires oxygen assistance. Therefore, in optimizing the operation and maintenance functions of the wastewater treatment system, it is necessary to have an exceptional understanding from the WWTP operator as the basis for the WWTP treatment planning process. Solid waste from hospital activities is estimated to cause health problems for living things and the risk of environmental pollution. B3 waste can come from medical waste, used batteries and lamps, expired medicines, used ink storage containers, leftover cleaning packages, and others.